IDENTIFIKASI FAKTOR SOSIAL YANG MEMPENGARUHI EFISIENSI PRODUKSI PADI PASANG SURUT DI KECAMATAN TANJUNG LAGO - Rori Fusilawati; Dessy Adriani; Elisa Wildayana (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2021)
This study aims to analyze the social factors that affect the efficiency of tidal rice production in Tanjung Lago District. Moreover, this study used a quantitative descriptive analysis. The sampling method used for this study was Sample Random Sampling . All of 84 paddy farmers in tidal lowland became respondents of this study. The data was analyzed using chi-square test. This study proved the social factors affetcted the efficiency of tidal rize production. Furthermore, the social factors affecting the affect the efficiency of tidal rice production is farming experience.This study found that efficiency could not be achieved only with terchnical factors such as agricultural input use amd ecology condition. The influence of social factor which is farming experience showed that the more farming experience, the better the technical cultivation carried out by farmers and encourage to acheive efficiency of rice production. The policy implications that could be constructed of this study are (1) Improving farmers’ experience through the latest production technology extension for rice farm (2) Mentoring in application of rice production technology.